Pseudomycetoma of the scalp caused by Microsporum canis, - Ligia Rangel Barboza Ruiz; Clarisse Zaitz; Rute Facchini Lellis; John Verrinder Veasey (Sociedade Brasileira de Dermatologia, 2020)
Abstract Pseudomycetoma is an extremely rare deep mycosis, caused by dermatophytic fungi that penetrate the tissue from infected follicles of tinea capitis. Both clinically and histopathology are similar to eumycetoma, being distinguished through the isolation of the fungus, which in the case of pseudomycetoma can be Microsporum spp. or Trichophyton spp. genre. We present a 24-year-old man with an exuberant tumor in the occipital region with fistula, whose histopathological examination evidenced grains composed of hyaline hyphae and the culture for fungi isolated the agent Microsporum canis. Combined treatment of surgical excision followed by oral griseofulvin for two years was performed, with resolution of the condition.